Inovasi dan Evaluasi Kurikulum Pendidikan Agama Islam dalam Pengembangan Pendidikan Masa Depan - Yenni, Yenni; Rosiana Syahbaniar; Muh Iqbal Muhidin; Dadang Sumarna (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This research aims to examine innovation and evaluation of the Islamic Religious Education (PAI) curriculum to support future educational development. The method used is a literature review, analyzing various scientific sources, including national and international journals, books, and recent research reports relevant to the topic. The study results indicate that PAI curriculum innovation needs to be oriented towards developing 21st-century competencies, integrating digital technology, and strengthening students' character and spiritual values. Furthermore, PAI curriculum evaluation should not only focus on cognitive aspects but also encompass affective and psychomotor aspects holistically. Other findings indicate that effective curriculum implementation requires the active role of teachers as learning innovators, support from educational policies, and the use of contextual learning media based on local wisdom. Curriculum evaluation also needs to be conducted continuously, using formative and summative approaches to ensure its relevance and effectiveness. Therefore, PAI curriculum innovation and evaluation are key to creating an education system that is adaptive, relevant, and able to meet future challenges. This research is expected to contribute to the development of a more progressive PAI curriculum oriented towards student needs in the era of globalization.